A decade of seed technology education in Malaysia - Chin, H. F.; Hor, Y. L. (International Seed Testing Association, 1981)
Seed technology was first introduced in 1968as a course in tertiary education. At present it isoffered both as an elective course for final year students in the Bachelor of Agricultural Science programme and also postgraduate studies in specialised areas of seed technology. Since 1975, seed technology has also been included in the second year Diploma of Agriculture programme. To date, 1562 diplomates, 141 graduates and 3postgraduates have undergone training in the various courses. Although no manpower survey on the needs for seed technologists has been carried out, the rapid expansion ofour agricultural programme and the recent launching ofthe national seed project indicate an increasing demand for trained personnel inthis field. Besides formal teaching in the university, workshops, symposia, short courses and field demonstrations are organised to cater for the needs of the farming community. With further development of the various courses backed up with research activities and a good extension programme, the University of Agriculture can be considered as a potential centre for seed industry development or an international centre for tropical seed technology.